(untitled) (Revista Interdisciplinar de Marketing, 2021)
Marketing studies have been focused on hegemonic narratives developed in the Global North. In the field of Marketing, there is a growing interest in the use of critical theories and historical perspectives. The decolonial perspective is presented by the author as a theory that could co-exist with pluralist critical historical studies in Marketing, particularly the Colonialities of Power, Knowledge and Being. The marketing field, particularly critical historical studies, should create an environment favorable to transdisciplinarity and transculturality, going beyond Eurocentric logics and Western paradigms, and establishing dialogues with silenced and marginalizes knowledges and perspectives.